Charles De Coster - Huysmans, Camille (London : Humphrey Milford, 1928)
Bibliotheek Camille Huysmans
In: Essays by divers hands, being the transactions of the Royal Society of Literature of the United Kingdom, new series, vol. 8
Frans
Monografie
Keywords: legenden; folklore; literatuur